Dampak Sharia Compliance, Kepercayaan, Kemudahan Penggunaan Dan Trend Terhadap Keputusan Pembelian Konsumen Muslim Milenial - Salihah Khairawati; Mu'tashim Billah Murtadlo; Sugeng Nugroho Hadi (ITB AAS INDONESIA Surakarta, 2023)
Many factors cause someone to shop online, ranging from low cost, quality of goods, trust, facilities, ease of transaction, to several other factors. This study uses four independent variables, namely sharia compliance (X1), trust (X2), convenience (X3), trend (X4), and online purchasing decisions as to the dependent variable (Y). This study aims to examine and analyze the Effect of Sharia Compliance, Trust, Ease, and Trends on Online Purchase Decisions through the Shopee Application on Yogyakarta students. This research is quantitative. Data collection techniques in this study using a questionnaire with the number of respondents 100 Yogyakarta students. The analytical tool used is multiple linear regression. Based on the results of the partial test, it shows that sharia compliance has a positive but not significant effect on online purchasing decisions. Meanwhile, trust, convenience, and trends have a positive and significant impact on online purchasing decisions. However, simultaneous testing shows that sharia compliance, trust, convenience, and trends have a positive and significant effect on online purchasing decisions through the Shopee Application for Yogyakarta students.